2017 IEEE 3rd VR Workshop on Sonic Interactions for Virtual Environments (SIVE) 2017
DOI: 10.1109/sive.2017.7901607
|View full text |Cite
|
Sign up to set email alerts
|

An approach to reducing distance compression in audiovisual virtual environments

Abstract: Perception of distances in virtual reality (VR) is compressed: objects are consistently perceived as closer than intended. Although this phenomenon has been well documented, it is still not fully understood or defined with respect to the factors influencing such compression. This is a problem in scenarios where veridical perception of distance and scale is essential. We report the results of an experiment investigating an approach to reducing distance compression in audiovisual VR based on a predictive model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Such a task can be timed and scored, and the user can be asked to describe their satisfaction and feelings to identify physical performance issues [33]. As another example, tasks involving actions that require users to reach out around their body to interact with nearby objects can be used to highlight unaddressed issues with distance compression, a frequent phenomenon within VR environments where objects are perceived by the user to be closer than their actual position [46]. Following a given task, a user may achieve high task performance scores but still report heavy cognitive overload (ie, mental exhaustion) while using the system, for example, finding that performing the task in VR was significantly more difficult than performing the same task with real objects or tools.…”
Section: Physical Performance Evaluationmentioning
confidence: 99%
“…Such a task can be timed and scored, and the user can be asked to describe their satisfaction and feelings to identify physical performance issues [33]. As another example, tasks involving actions that require users to reach out around their body to interact with nearby objects can be used to highlight unaddressed issues with distance compression, a frequent phenomenon within VR environments where objects are perceived by the user to be closer than their actual position [46]. Following a given task, a user may achieve high task performance scores but still report heavy cognitive overload (ie, mental exhaustion) while using the system, for example, finding that performing the task in VR was significantly more difficult than performing the same task with real objects or tools.…”
Section: Physical Performance Evaluationmentioning
confidence: 99%
“…Prior research shows that a problem [13] exists where humans inaccurately perceive the depth of objects in virtual environments [8]. The reasons are summarized by Lawson et al [15], which in turn are drawn from Renner et al's research [20].…”
Section: The Problem Of Depth Perception Distortionmentioning
confidence: 99%
“…However, strides have been made through improved technology to rectify depth perception distortion. It is generally understood that distance is compressed in virtual environments [8], [13], [25], [21], meaning users tend to perceive virtual objects in relation to themselves (egocentric space) as closer than their actual distance. Similarly, Rolland et al [22] found that using simple virtual objects such as a cube or a cylinder led to expanded perceptual distortion rather than compressed.…”
Section: The Problem Of Depth Perception Distortionmentioning
confidence: 99%
See 2 more Smart Citations